Implementasi Media Pembelajaran Berbasis Teknologi serta Pengaruhnya terkait dengan tingkat minat belajar peserta didik dalam mata pelajaran Pendidikan Agama Islam - Indah Citra Soleha; Ahda Khilwa Sabrina; Hafizoh Halim; Muhammad Rizky Ihsan; Rabahul Sri Nate; Muhammad Narendra; Muhammad Galuh Dwi Putra; Sabrun Jamil (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The combination of information and communication technology into education have brought about meaningful changes in learning processes, especially within Islamic Religious Education. Technology-based learning media has become an alternative that is considered capable of increasing students' interest in learning. This research study to analyze the influence on the effect of digitally-assisted learning resources on students’ engagement in Islamic Religious Education. This research adopts a quantitative approach employing a survey method. Questionnaires were employed to collect data, and the results were analyzed utilizing appropriate statistical procedures. The findings indicate that the utilization of technology-based learning media positively influences students’ learning interest, as evidenced by increased attention and active involvement in the Islamic Religious Education learning process. Overall, the findings demonstrate that the adoption of technology in Islamic Religious Education learning constitutes an effective approach to enhancing learning quality in response to contemporary educational challenges